Genetic polymorphisms of proinflammatory (IL-1β) cytokines in Malay male drug abusers with Hepatitis C infection - Lansayan, Jalviana (2022)
The Hepatitis C virus (HCV) infection frequently results in liver conditions such fibrosis, cirrhosis, and hepatocellular carcinoma, therefore, it poses a serious risk to the general public health. Furthermore, the incidence of HCV infection transmission is concerning among drug abusers. The intercellular mediators of inflammation, cytokines, are byproduct in viral control and the liver damage brought on by hepatitis C virus infection. IL-1β, particularly, is a proinflammatory cytokine that is secreted during the innate and adaptive immune response that is pivotal in chronic inflammatory diseases. Studies have reported the association of this cytokine and susceptibility of chronic HCV infection. Therefore, the purpose of the study was to investigate the role of IL-1β polymorphisms (rs16944 and rs1143634) in regard to chronic hepatitis C infection susceptibility. A total of 48 Malay male drug abuser were involved in this case-control retrospective study. The genomic DNA was extracted from whole blood sample then analyzed through polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) for the IL-1β rs16944) and IL-1β (rs1143634) polymorphisms. The analysis of IL-1β (rs1143634) showed that CC genotype was common in both case and control group. However, no statistical significance was achieved. This research concluded that there was no association between the polymorphisms (rs16944 and rs1143634) and susceptibility to hepatitis C infection among Malay male drug abuser.